Firm Size Effect and Cross-Sectional Returns: A Study of Automobile Sector - Palash Bairagi; Anindita Chakraborty (Journal of Advanced Research in Accounting and Finance Management, 2019)
The size effect is an anomaly in the stock market which shows the volatility of the market. The study has been conducted on yearly basis data relating to market capitalization, earning per share, book value and daily returns for the period of 2005 to 2014 of selected Indian automobile companies which are listed in Bombay Stock Exchange. The study highlights individual and market returns of the companies and measures the impact of firm size on cross-sectional returns. The study also tries to stretch on comparing return and size of the company across industry and concludes that small cap securities generate greater returns than large- cap and medium-cap securities. How to cite this article: Bairagi P, Chakraborty A. Firm Size Effect and Cross-Sectional Returns: A Study of Automobile Sector. J Adv Res Acct Fin Mgmt 2019; 1(1): 1-4.